Substance misuse, mental health problems and recurrent child maltreatment - Laslett, Anne-Marie; Room, R.; Dietze, P. (2014)
Purpose: The purpose of this paper is to determine whether the diagnosis of both carers' mental health problems and substance misuse increase the likelihood of recurrent child maltreatment over and above the individual effects of these factors. Design/methodology/approach: Retrospective secondary data analysis of 29,455 children where child maltreatment was confirmed in the Victorian child protection system between 2001 and 2005. Recorded mental health, alcohol misuse and other drug misuse variables were entered into multivariate logistic regression models predicting repeated child maltreatment. Interactions and a range of other child, carer and socio-economic factors were included in these models. Findings: Carer alcohol misuse, other drug misuse and mental ill health all independently predicted recurrent child maltreatment. The presence of both other drug misuse and mental ill health increased the likelihood that recurrent child abuse was recorded over the likelihood that mental health alone predicted recurrent child maltreatment, and while alcohol misuse had an effect when there was no mental health condition recorded it did not have an additional effect when there was evidence of mental health problems. Research limitations/implications: Children in families where there is both mental health problems and other drug use problems are at greater risk of repeated maltreatment than where there is evidence of mental health problems or other drug use alone. Where there was evidence of carer mental health problems, alcohol misuse did not add to this likelihood. However, the effect of mental health and other drug use was similar in size to the effect of alcohol misuse alone. Originality/value: These findings add to understandings of the effects of co-occurring mental health problems and substance misuse on recurrent child maltreatment and differentiate between cases that involve alcohol and other drug misuse.